[(177)Lu]-DOTA(0)-Tyr(3)-octreotate: A Potential Targeted Radiotherapeutic for the Treatment of Medulloblastoma - Vaidyanathan, Ganesan (2010)
Medulloblastoma, the most common pediatric brain tumor, is difficult to treat because conventional therapeutic approaches result in significant toxicity to normal central nervous system tissues, compromising quality of life. Given the fact that medulloblastomas express the somatostatin subtype 2 receptor, [(177)Lu-DOTA(0),Tyr(3)]octreotate ([(177)Lu]DOTA-TATE) could be a potentially useful targeted radiotherapeutic for the treatment of this malignancy. The current study was undertaken to evaluate this possibility in preclinical models of D341 MED human medulloblastoma by comparing the properties of [(177)Lu]DOTA-TATE to those of glucose-[(125)I-Tyr(3)]-octreotate ([(125)I]Gluc-TOCA), a radiopeptide previously shown to target this cell line. In vitro assays indicated that both labeled peptides exhibited similar cell-associated and internalized radioactivity after a 30-min incubation at 37°C; however, at the end of the 4 h incubation period, the internalized radioactivity for [(177)Lu]DOTA-TATE (6.22 " 0.75%) was nearly twice that for [(125)I]Gluc-TOCA (3.16 " 0.27%), with similar differences seen in total cell-associated radioactivity levels. Consistent with the results from the internalization assays, results from paired-label tissue distribution studies in athymic mice with subcutaneous D341 MED medulloblastoma xenografts showed a similar degree of tumor accumulation for [(177)Lu]DOTA-TATE and [(125)I]Gluc-TOCA at early time points but by 24 h, a more than 5-fold advantage was observed for the (177)Lu-labeled peptide. Tumor-to-normal tissue ratios generally were more favorable for [(177)Lu]DOTA-TATE at all time points, due in part to its lower accumulation in normal tissues except kidneys. Taken together, these results suggest that [(177)Lu]DOTA-TATE warrants further investigation as a targeted radiotherapeutic for medulloblastoma treatment.